Mengatasi Kenakalan Remaja Melalui Pendidikan Agama Islam: Peran Guru yang Signifikan di SMP Negeri 26 Makassar - Nur Afia T; Nurul Mukhlisa; Findi Rahmawati; Sam’un Mukramin (Jurnal Ilmu Pendidikan dan Sosial, 2024)
In today’s world, juvenile deliquency is becoming an increasingly troubling social problem. These trends often include acts such as drug use, fighting, promiscuity, and other illegal activities. Teachers play an important role in addresing this problem in the context of islamic education. Knowing students is a very important and interesting issue to discuss because someone whose name is student is part of the younger generation and in the eyes of natioon, state and religion. In this study, researchers use a qualitative descriptive approach, which is a research procedure based on descriptive data in the form of oral or written  words from reseach subjects or informants who have been observed and have the characteristics that the data provided is original data according to situations and conditions that cannot be manipulated and uses systematic and accountable methods. Based on the results of research obtained by reseachers through observation and interviews with informants, there are several forms of juvenile delinquency that occur in SMP Negri 26 Makassar : 1) noisy in class during class hours, 2) this turbing friends who are focused on learning activities, 3) after skipping lessons, 4) smoking. The eforts of religus education teachers in overcoming students delinquency are to pay more attention to children who are especially “naughty” (seeking attention).